Enhancing the Structure and Performance of P3HT/PC70BM Polymer Solar Cells with N-Dodecylthiol - (:unkn) unknown (My University, 2014)
Polymer solar cells (PSCs) have attracted much attention because of their low cost, high flexibility, lightweight, and large surface area compared to long-established silicon solar cells. In most cases, bulk heterojunction type solar cells (BHJ) use a phase-separated blend of organic electron donor and acceptor components, where a conductive polymer is the donor and a fullerene derivative is the acceptor. To achieve high performance BHJ-type PSCs, the electron-donating conjugated polymer needs to be strong absorbent of a wide range of solar light waves and possess good hole mobility. This results in short-circuit current (Jsc) and/or open-circuit voltage (Voc) at their optimum values. In this research, n-dodecylthiol (0-5% vol.) was added to P3HT/PC70BM polymer solution to improve the crystallinity of P3HT and enhance the P3HT/PC70BM phase separation. Higher P3HT crystallinity reduces the amount of PCBM dissolved in the amorphous regions of P3HT, thus promoting the aggregation of PC70BM, which contributes to PC70BM/P3HT phase separation. Adding 2% n-dodecylthiol to the active layer resulted in forming the smallest polymer crystallites size L, which was nearly 11.2 nm at optimum annealing conditions at (150C for 30 min in a vacuum atmosphere). The smaller crystallite size suggests a shorter path of the charge carriers between P3HT backbones, which increases the short circuit current (Jsc) and decreases the open circuit voltage (Voc) in the solar cells. UV-Vis and EQE analysis showed enhancement of self-organization ability, which led to improved P3HT crystallinity and intensified phase separation of P3HT/PC70BM in polymer films. EQE increased due to enhanced hole and electron polaron mobility with n-dodecylthiol. AFM images showed increased surface roughness with adding n-dodecylthiol, yielding more spaces for P3HT crystallites to form, and hence resulting in higher crystallinity. DLS analysis of P3HT:PC70BM:n-dodecylthiol dissolved in chlorobenzene solution showed an increase of aggregate size by adding n-dodecylthiol; which confirms the SEM images. This also shows that n-dodecylthiol does not enhance the dispersion of P3HT:BC70BM in the chlorobenzene solution. Also, it shows that the more n-dodecylthiol is added, the more aggregation will be formed. In addition, increasing mixing time and temperature improves the mixing process and results in smaller aggregates. Kinetics of cold crystallinity for P3HT:PC70BM using Avrami model showed an overall increase in crystallization rate (1/t0.5) with increasing the annealing temperature. The increase in phase separation balancing for exciton dissociation and charge transport and collection resulted in a 33% increase in solar cell efficiency when the volume fraction of n-dodecylthiol is 2%. The enhancement of cell performance after thermal annealing deteriorated at temperatures higher than 150 C.